A dominant‐negative form of Arabidopsis AP‐3 β‐adaptin improves intracellular pH homeostasis. (21st March 2013) - Niñoles, Regina; Rubio, Lourdes; García‐Sánchez, María J.; Fernández, José A.; Bueso, Eduardo; Alejandro, Santiago; Serrano, Ramón
Summary: Intracellular pH (pHi ) is a crucial parameter in cellular physiology but its mechanisms of homeostasis are only partially understood. To uncover novel roles and participants of the pHi regulatory system, we have screened an Arabidopsis mutant collection for resistance of seed germination to intracellular acidification induced by weak organic acids (acetic, propionic, sorbic). The phenotypes of one identified mutant, weak acid‐tolerant 1‐1D ( wat1‐1D ) are due to the expression of a truncated form of AP‐3 β‐adaptin (encoded by the PAT2 gene) that behaves as a as dominant‐negative. During acetic acid treatment the root epidermal cells of the mutant maintain a higher pHi and a more depolarized plasma membrane electrical potential than wild‐type cells. Additional phenotypes of wat1‐1D roots include increased rates of acetate efflux, K + uptake and H + efflux, the latter reflecting the in vivo activity of the plasma membrane H + ‐ATPase. The in vitro activity of the enzyme was not increased but, as the H + ‐ATPase is electrogenic, the increased ion permeability would allow a higher rate of H + efflux. The AP‐3 adaptor complex is involved in traffic from Golgi to vacuoles but its function in plants is not much known. The phenotypes of the wat1‐1D mutant can be explained if loss of function of the AP‐3 β‐adaptin causes activation of channels or transporters for organic anions (acetate) and for K + at the plasma membrane, perhaps through miss‐localization of tonoplast proteins. This suggests a role of this adaptin in trafficking of ion channels or transporters to the tonoplast.